Invitation to treat from the perspective of comparative and Serbian law - Dzipkovic, Ksenija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The author begins with an analysis of an invitation to treat, its characteristics and legal consequences. Its peculiarities are also highlighted through comparison with other contractual initiatives – an offer, an invitation to negotiations, a unilateral promise, and a public promise of reward. The central part of the work is devoted to the analysis of cases that are qualified as the invitation to treat in Serbian, French, Swiss, German, and English law. These are advertisements, display of goods with or without a marked price, auctions, and tenders. The legal nature of online advertisements and online auctions is presented as well. The author explains the reasons for specific comparative law solutions and draws conclusions that justify the qualification of contractual initiatives as invitations to treat or she criticizes the solutions presented. Also, attention is devoted to the analysis of Serbian positive law since its provisions are compared with the solutions of other legal systems. Furthermore, some of those provisions served as a model for Serbian legislator.